Respuesta :

Answer: Option G

[tex]a_6 = -2048[/tex]

Step-by-step explanation:

The geometric series have the following form:

[tex]a_n = a_1 (r) ^ {n-1}[/tex]

Where [tex]a_1[/tex] is the first term of the sequence and r is the common radius.

In this case we know that

[tex]a_1 = -2\\\\r = 4[/tex]

So:

[tex]a_n = -2(4) ^ {n-1}[/tex]

To find the sixth term [tex]a_6[/tex], substitute [tex]n = 6[/tex] in the equation.

[tex]a_6 = -2 (4) ^ {6-1}\\\\a_6 = -2 (4) ^ 5\\\\a_6 = -2048[/tex]

ACCESS MORE